(untitled) (Jurnal Ekonomi dan Kebijakan Pembangunan, 2024)
This study aims to explore the influence of corruption on productivity in countries trapped in the Middle-Income Trap (MIT). The study utilizes panel data from 2003 to 2019 covering 50 countries confirmed to be trapped in the MIT based on various definitions in Pruchnik and Zowczak’s (2017) research. Productivity is proxied by Total Factor Productivity (TFP), while the Control of Corruption index is used to depict the level of corruption. Findings indicate a significant negative impact of corruption on productivity in MIT-trapped countries, consistent with the "sand on the wheel" hypothesis. Additionally, based on estimated TFP growth values, China has the highest likelihood of escaping the MIT compared to other studied countries. This study also employs instrumental variable (IV) regression to anticipate endogeneity issues between corruption and productivity, yielding consistent results with previous findings. Therefore, addressing corruption should be a priority in a country’s efforts to exit the MIT, as it has the potential to enhance the country’s productivity.